2017
DOI: 10.1016/j.cels.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Feedback and Buffering in Cellular Homeostasis

Abstract: Buffering, the use of reservoirs of molecules to maintain concentrations of key molecular species, and negative feedback are the primary known mechanisms for robust homeostatic regulation. To our knowledge, however, the fundamental principles behind their combined effect have not been elucidated. Here, we study the interplay between buffering and negative feedback in the context of cellular homeostasis. We show that negative feedback counteracts slow-changing disturbances, whereas buffering counteracts fast-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(90 citation statements)
references
References 57 publications
0
90
0
Order By: Relevance
“…These properties might prove to be essential for applications in metabolic engineering and cellular therapeutics where different considerations and tradeoffs might be at play, and hence different combinatorial variations of the three terms (P, I, or D) might be needed and appropriate. They also might facilitate mixing and matching our designs with those of others, for example using implementation of a naturally occurring derivative motif that was recently analyzed (Hancock et al, 2017) and shown to exhibit excellent noise suppression characteristics at high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…These properties might prove to be essential for applications in metabolic engineering and cellular therapeutics where different considerations and tradeoffs might be at play, and hence different combinatorial variations of the three terms (P, I, or D) might be needed and appropriate. They also might facilitate mixing and matching our designs with those of others, for example using implementation of a naturally occurring derivative motif that was recently analyzed (Hancock et al, 2017) and shown to exhibit excellent noise suppression characteristics at high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Any feedback control system can be analyzed using CoRa, providing a unifying framework under which different feedback mechanisms can be rigorously compared. In fact, we were able to rapidly analyze a large number of distinct feedback control motifs proposed in the literature [2,4,6,7,11,13,15] (Fig. 3; Supplementary Information).…”
Section: /7mentioning
confidence: 99%
“…Determining the design principles behind biological regulation is important for understanding the principles of life, treating complex diseases, and creating de novo synthetic biology [20]. A significant amount of research into this topic has focussed on feedback regulation [2,8,9,18,20,34,35,36,43], a ubiquitous mechanism in biology that acts via biological actuators, such as regulated enzymes [17,38]. But there is a crucial open challenge to determine the underlying principles for biological regulation beyond feedback [20].…”
Section: Introductionmentioning
confidence: 99%
“…But there is a crucial open challenge to determine the underlying principles for biological regulation beyond feedback [20]. Buffering-the use of reservoirs of molecules to maintain molecular concentrations-is another widespread mechanism for biological regulation [17,38]. Despite its importance, buffering has received considerably less attention than feedback.…”
Section: Introductionmentioning
confidence: 99%